2022
DOI: 10.1101/2022.12.01.518580
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiomic Profiling of Human Clonal Hematopoiesis Reveals Genotype and Cell-Specific Inflammatory Pathway Activation

Abstract: Clonal hematopoiesis (CH) is an age-associated phenomenon that increases risk for hematologic malignancy and cardiovascular disease. CH is thought to increase cardiovascular disease risk through inflammation in the peripheral blood1. Here, we profile peripheral blood gene expression in 104,566 single cells from a cohort of 17 CH patients and 6 controls. We discovered that patients harboring DNMT3A and TET2 CH mutations at baseline and in response to IL-6 stimulation confer a pro-inflammatory profile to CD14+ m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
2
2
0
Order By: Relevance
“…CH mutations were found in affected arteries at similar levels found in peripheral blood, similar to the finding that CH clones can be also detected in atherosclerotic plaques 38. Monocytes from patients with GCA with CH secreted higher levels of chemokines that modulate macrophage proinflammatory signalling pathways (MCP1, MIP1b and MIP1a), findings consistent with recently reported study that identified pathways involved in macrophage function as a mediator of inflammation linked to TET2 mutations in monocytes 37. These chemokines regulate monocyte/macrophage migration from blood across vascular endothelium during immunological surveillance of tissue in response to inflammation, suggesting CH may contribute to vascular inflammation 39 40.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…CH mutations were found in affected arteries at similar levels found in peripheral blood, similar to the finding that CH clones can be also detected in atherosclerotic plaques 38. Monocytes from patients with GCA with CH secreted higher levels of chemokines that modulate macrophage proinflammatory signalling pathways (MCP1, MIP1b and MIP1a), findings consistent with recently reported study that identified pathways involved in macrophage function as a mediator of inflammation linked to TET2 mutations in monocytes 37. These chemokines regulate monocyte/macrophage migration from blood across vascular endothelium during immunological surveillance of tissue in response to inflammation, suggesting CH may contribute to vascular inflammation 39 40.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings support the concept that CH primes myeloid cells to a pro-inflammatory phenotype,37 which potentially may modulate an underlying inflammatory process and alter the course of disease. Patients with GCA with CH had increased myeloid cell burden, and monocytes, NK cells and T lymphocytes displayed an activated phenotype marked by high expression of CD10, CD11b and CD16.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…8,14 This suggests that the contribution of somatic mutation to GCA may be mediated by myeloid cells, as have emerged in the mechanistic evaluation of a broad array of other TET2-associated conditions. 8 In other model systems, Tet2-deficient monocytes and macrophages display enhanced response to inflammatory stimuli, especially enriched for increased IL-1B and prolonged IL-6 production, [8][9][10]15,16 cytokines well recognized to be elevated in GCA monocytes. 2 More recently, increased proportions of dysregulated immature neutrophils have been described in a humanized mouse model of TET2 CH, which have also been directly implicated in GCA pathogenesis through damage to the endothelium.…”
Section: Discussionmentioning
confidence: 99%